Transformational Leadership for School Well-Being: Building a Positive Learning Environment - Sutinah, Titin; Ismaya, Bambang; Sholeh, Slamet (Research Horizon, 2025)
Transformational leadership plays a crucial role in enhancing school well-being by influencing the behavior, motivation, and moral commitment of staff. This study aims to analyze how the principal’s transformational leadership contributes to school well-being in a holistic sense and how this leadership style fosters a positive learning environment. A qualitative case study approach was used, with data collected through observations, in-depth interviews with the principal, teachers, supervisors, and educational staff, as well as analysis of school reports, quality assurance documents, supervision records, and meeting minutes. The findings indicate that the principal effectively applied the four core dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. These practices built trust, motivation, creativity, and emotional support among teachers, improving the overall well-being of the school community. The integration of transformational leadership with systematic quality improvement processes created a sustainable culture of quality and a collaborative, positive, and religious learning environment. The study concludes that transformational leadership significantly strengthens school well-being and fosters a conducive atmosphere for learning.